American Humanist Association v Birdville Independent School District (851 F.3d 521): United States Court of Appeals for the Fifth Circuit: Smith CJ writing in a unanimous decision: 20 March 2017. (5th June 2018) - Unknown
ABSTRACT: Federal constitutional law – First Amendment – Establishment Clause – Free Speech – Public school district policy inviting students to deliver a statement, which could include a prayer, during monthly school-board meetings – Content of statements at the discretion of students subject to requirement they be relevant and not obscene – Board selecting speakers randomly from list of volunteers – Board meetings held on District property – Former student belonging to American Humanist Association challenged public school district policy – Complaining at invitation to 'join', 'stand', or 'bow' in participation – Trial court refusing challenge to school policy – Whether school board prayer is more akin to legislative prayer or school prayer – Whether public school policy inviting students to deliver statements violation of Establishment Clause – US Const Amend 1